Analysis of power system event using synchronized PMUs in Thailand power network - I. Ngamroo (2018)
This paper applies the synchronized phasor measurement units (PMUs) based wide-area monitoring system to analyze the power system event under the occurrence of large disturbance. The salient feature of the monitoring system is the convenient installation of PMU at 220 V home outlet. The power system event given here is the tripping of High-Voltage Direct Current (HVDC) link between Thailand and Malaysia due to the fault in a thyristor room at Khlong Ngae converter station of Thailand side on July 22, 2005. The discrete wavelet decomposition and short-time Fourier Transform have been applied to analyze the characteristic of the inter-area oscillation between central and southern areas in both time and frequency domains. Analyzed results based on PMUs data are consistent with the actual tie-line power flow between both areas.